The use of analytical procedures to detect Earning Management Practices - سلمان عامر محمد; كندوري عماد محمد (Journal of Economics and Administrative Sciences, 2013)
That analytical procedures are of analytical tools important because it gives assurance to the auditor-free financial statements of the economic units replace the audit of cases offraud and errors and distortions, and thereby to increase the effectiveness of the audit process and confirm the possibility oftrust and reliance on the financial statements that Adfgaha auditor. Inspite of identify evidence of proof necessary to enhance the auditor’s opinion the results reached in the audit process but it often does not include the evidence on the discovery of material misstatement of the financial statements that lead to earning management. In this research aims to identify and define the appropriate analytical procedures that require the auditor to use to detectpotential errors in the paragraphs of the core financial statements of the economic units replace the audit and to identify the most important factors that influence this.